2010
DOI: 10.1103/physrevd.81.124037
|View full text |Cite
|
Sign up to set email alerts
|

Primordial perturbations from multifield inflation with nonminimal couplings

Abstract: Realistic models of particle physics include many scalar fields. These fields generically have nonminimal couplings to the Ricci curvature scalar, either as part of a generalized Einstein theory or as necessary counterterms for renormalization in curved background spacetimes. We develop a gauge-invariant formalism for calculating primordial perturbations in models with multiple nonminimally coupled fields.We work in the Jordan frame (in which the nonminimal couplings remain explicit) and identify two distinct … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 54 publications
1
58
0
Order By: Relevance
“…Recent analyses [41][42][43][44][45][46][47][48] of multifield models showed that unlike the single-field models they generically provide density (entropy) perturbations which can induce the curvature perturbation to evolve beyond the cosmological horizon in the process of inflation [49]. Evolution of density perturbations in multifield models should be studied in order to analyze new features in the observables such as non-Gaussianities [50] which are absent in the single-field inflationary models.…”
Section: Jhep12(2017)036mentioning
confidence: 99%
“…Recent analyses [41][42][43][44][45][46][47][48] of multifield models showed that unlike the single-field models they generically provide density (entropy) perturbations which can induce the curvature perturbation to evolve beyond the cosmological horizon in the process of inflation [49]. Evolution of density perturbations in multifield models should be studied in order to analyze new features in the observables such as non-Gaussianities [50] which are absent in the single-field inflationary models.…”
Section: Jhep12(2017)036mentioning
confidence: 99%
“…We have investigated numerically the effects of this coupling on the power spectrum of primordial fluctuations. It has previously been shown that a non-minimally coupled scalar field can induce changes in the curvature perturbation on superhorizon scales via the introduction of terms proportional to f,ḟ andf in the non-adiabatic pressure perturbation, δP nad [11]. Here, we have quantified this effect.…”
Section: Resultsmentioning
confidence: 88%
“…Models with non-minimally coupled scalar fields, on the other hand, will produce a distinct source of entropy perturbations, arising due to the coupling of the scalars. In the model we present above, it is expected that, after inflation has ended and during the reheating phase, these entropy perturbations can become sizeable due to the fact thatḟ andf no longer need to remain small [11]. It is these non-adiabatic pressure perturbations, and the resulting amplification of the power spectrum, that we will investigate in the remainder of the paper.…”
Section: Theory and Analytical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are at least two ways to solve the problem of late-time acceleration, namely modification of the gravitational theory orthe introduction of some exotic source of gravity, which is commonly called Dark Energy (DE). As the models of dark energy are customarily used not only canonical fields with the modified potential of self-interaction or the combination of fields with some physically or phenomenologically founded types of interaction between the components [5][6][7][8]. Among a great number of approaches for solving the problem of dark energy, we can mention the field theory with non-canonical kinetic term in cos-mology [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%